The city and its uncertain walls - Murakami, Haruki, 1949- (Alfred A. Knopf, 2024)
"The long-awaited new novel from Haruki Murakami, his first in six years, revisits a town his readers will remember, a place where a Dream Reader reviews dreams and where our shadows become untethered from our selves. A love story, a quest, an ode to books and to the libraries that house them, and a parable for these strange post-pandemic times, The City and Its Uncertain Walls is a singular and towering achievement by one of modern literature's most important writers"--